Marketing Determinants and Teachers’ Job Performance in University Of Calabar - Nigeria - Sunday Etim; Kajang, Glory; Lane, Joshua (British Journal of Marketing Studies, 2019)
The study examined marketing determinants and teachers’ job performance in University of Calabar – Nigeria. The objective of the study was to survey marketing determinants that can influence teachers’ job performance in University of Calabar. The study adopted survey research design. The population of the study was 124 academic staff of Faculty of Management Sciences and the sample size was 95 obtained by Taro Yamane method. The findings of the study revealed that there is a significant relationship between processes and teachers’ job performance, and there is a significant relationship between physical evidence and teachers’ job performance in the University of Calabar – Nigeria. The study recommended that federal government and relevant agencies as well as University management ensure prompt and timely payment of all financial benefits of teachers to boost teachers’ morale and improve welfare thereby ensuring job satisfaction to promote performance. Teachers should be provided with physical enabling environment to motivate teachers to put in the best for the system.